Formulation and evaluation of extended release trilayered matrix tablets of rasagiline mesylate by geomatrix - B. Prabhakar Reddy; D.V. R. N. Bhikshapathi (International Journal of Pharmacy and Analytical Research, 2022)
The main objective of the present study was to prepare controlled release (CR) matrix trilayer tablet of rasagiline mesylate to achieve zero-order drug release for controlled plasma concentration. Twenty seven formulations (F1-F27) for middle layer were prepared by direct compression method using 3 3 response surface method (3 variables and 3 levels of polymers) by using design of experiment software with polymers like different HPMC grades. The barrier layers was formulated employing hydrophobic swellable polymer Polyox WSR 303, xanthan gum and EC. The procedure adopted to make the compacts was via direct compressions. The tablets were also evaluated for physicochemical characteristics and release kinetics and it was satisfactory. The developed drug delivery systems showed prolonged drug release rates over a period of 24 h. The release profile of the optimized formulation (HF17) was described by the zero-order and Higuchi model. These results also demonstrated the suitability of rasagiline mesylate three-layered tablet formulation of to provide controlled release for prolonged period of time and improved linearity for rasagiline mesylate in comparison to marketed product in the management of Parkinson’s disease.